Day-to-day routing adjustment behaviour - Eng, Yu Kai (2019)
In a traffic equilibrium state, travellers’ routing choices are such that no one is willing to change their route. As explained by Wardrop’s First Principle, travellers make traffic decisions in a manner that results in every Origin-Destination (OD) pair having the shortest and most optimised travel time. However, when there is a change in the transport network, for example an addition or removal of road (i.e. a new link is added or removed), travellers will theoretically alter their routing choices and eventually reach a new equilibrium in the long run. Routing choices made by individuals are often affected by many factors like cost of travel, crowdedness of the road, etc. Although the extent to which each factor affects the decision made by travellers is hard to quantify, it is an important piece of information to authorities that are tasked to manage the transport network. This is because with proper understanding of how travellers behave, it will allow traffic management measures to be executed more effectively and efficiently. The aim of this research paper is to analyse the day-to-day routing adjustment behaviour of travellers in Singapore. A survey was calibrated for this research project for this study. A recent case study on the operation of Lornie Highway was also done in this project with an aim to improve accuracies of results. Results and analysis collected from the surveys will be presented in this paper to study the routing adjustment behaviour and process of travellers.